2016
DOI: 10.2146/ajhp150519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist-driven protocol to decrease proton pump inhibitor use in non-intensive care hospitalized adults

Abstract: The pharmacist-driven protocol described in this study decreased PPI use in non-ICU hospitalized adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Furthermore, PPIs are also available for over-the-counter (OTC) purchase as part of self-care; however, with recent concerns about impurities of ranitidine and nizatidine (both H 2 RAs), patients may preferentially purchase OTC PPIs rather than H 2 RAs [112,113]. Therefore, a difficult and frequently-encountered clinical situation is not being able to determine why a patient is taking AST as the patient may not know or remember the indication, and/or the indication was never documented [38]. Prescribers encountering these patients in various settings may fear negative consequences or may not have adequate time and/or receive proper reimbursement to address AST appropriateness [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PPIs are also available for over-the-counter (OTC) purchase as part of self-care; however, with recent concerns about impurities of ranitidine and nizatidine (both H 2 RAs), patients may preferentially purchase OTC PPIs rather than H 2 RAs [112,113]. Therefore, a difficult and frequently-encountered clinical situation is not being able to determine why a patient is taking AST as the patient may not know or remember the indication, and/or the indication was never documented [38]. Prescribers encountering these patients in various settings may fear negative consequences or may not have adequate time and/or receive proper reimbursement to address AST appropriateness [32].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate prescribing within the hospital setting and a growing list of serious adverse events associated with PPIs have prompted health care providers to develop various strategies to reduce inappropriate use [31]. These include deprescribing [12,[32][33][34], applying SUP guidelines, checklists and protocols [35][36][37][38], completing medication reconciliation activities [39,40], communicating concerns in-person and/or electronically [41][42][43][44], academic detailing [45], and educational campaigns [36,44,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…A multicentre, cluster randomized, controlled trial showed that special pharmacists could play important role in reducing the frequency of a series of clinically important prescription and medication monitoring errors [ 21 ]. Recently, studies showed that pharmacist intervention decreased PPIs use in non-ICU hospitalized patients and overutilization of SUP in medical and surgical ICU [ 22 , 23 ]. A retrospective study discovered that the relative reduction in the rate of inappropriate SUP in general ward patients was 83.5% after implementing pharmacist SUP managed program [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This estimation was based on three studies, one of which was from previous internal data of a prior study, that were all quasi-experimental in design with a primary end point focusing on the difference in inappropriate continuation of a medication post implementation of an intervention. [30][31][32] Data results are presented as median with interquartile ranges (IQR). Continuous variables were compared using a Mann-Whitney U test.…”
Section: Discussionmentioning
confidence: 99%